Effects of altitudinal gradients on leaf area index, soil microbial biomass C and microbial activity in a temperate mixed forest ecosystem of Northwestern Turkey - Bolat, İlyas; Ozturk, Melih; Öztürk, Melih; Bolat, İlyas (Sisef-Soc Italiana Selvicoltura Ecol Forestale, 2017)
A high leaf area index (LAI) can provide indications of high fertility, such as optimal health and productivity in forest ecosystem. Yet, studying the microbial biomass and inherent activity in any forest ecosystem may enable better understanding of the role of microorganisms in soil quality and nutrient cycling. This study was carried out in the western Black Sea region of Turkey with the aim to determine the influence of elevation on LAI, microbial biomass and activity in a mixed forest ecosystem. Marked differences in the LAI, light transmission, soil temperature, Corg/Ntotal ratio, and microbial properties were found at sites sampled at different elevations along an altitudinal gradient (i.e., 1200, 1300 and 1400 ma.s.l.). The LAI was statistically (P < 0.05) higher at 1300 (3.28 m(2) m(-2)) and 1400 m (3.20 m(2) m(-2)) elevations compared to 1200 m (2.84 m(2) m(-2)) elevation, whereas the light transmission was statistically (P < 0.05) lower at 1300 and 1400 m elevations than that at 1200 m elevation. The amount of microbial biomass C at 1300 m (892.26 mu g g(-1)) and 1400 m (725.99 mu g g(-1)) elevations was significantly (P < 0.05) higher than that at 1200 m (650.84 mu g g(-1)) elevation. Basal respiration did not vary significantly (P > 0.05) along the altitudinal gradient. An increase in respiration per unit biomass (i.e., increasing the metabolic quotient - qCO(2)) was also found in the sampling sites at 1200 ma.s.l. There was a positive relationship between the microbial biomass C and LAI (r = 0.612, P < 0.01) and negative relationship between the qCO(2) and LAI (r = -0.592, P < 0.01). Our results showed that the elevation gradient has a significant influence on the LAI, microbial biomass C and microbial activity in the forest stand type analyzed. A subdivision of the forest stand types into different sub-types according to their productivity and development is advisable and recommended for forest management and administration purposes.
Keywords: Basal Respiration; Bornmullerian Fir; C-Mic/C-Org Percentage; Metabolic Quotient (Qco(2)); Oriental Beech; Soil